Immunogenicity of PE18, PE31, and PPE26 proteins from Mycobacterium tuberculosis in humans and mice - García-Bengoa, María; Vergara, Emil Joseph; Tran, Andy C.; Bossi, Lorenzo; Cooper, Andrea M.; Pearl, John E.; Mussá, Tufária; von Köckritz-Blickwede, Maren; Singh, Mahavir; Reljic, Rajko (Frontiers in Immunology, 2023)
The large family of PE and PPE proteins accounts for as much as 10% of the genome of the pathogen M. tuberculosis. We explored the immunogenicity of three of these proteins, PE18, PE31, and PPE26, in humans and mice. We found that all three proteins are immunoreactive with sera from TB patients, IGRA+ household contacts, as well as IGRA-BCG vaccinated healthy controls from the TB endemic country Mozambique. Likewise, all three antigens could induce antigen-recall responses in PBMC from all groups. The proteins also induced proliferation of peripheral blood mononuclear cells from healthy unexposed individuals.Using systemic priming and intranasal boosting with each protein formulated with the Quil-A adjuvant in mice, we found that all three antigens induced IgG antibody responses in sera and, predominantly IgG rather than IgA responses in bronchoalveolar lavage. Antigen-specific CD4+ and CD8+ effector memory T cell responses were also induced in the spleen, with PE18 also able to induce tissue-resident memory T cells in the lungs. To examine the protective capacity of these induced immune responses, we challenged immunised mice with low-dose aerosol of M. tuberculosis strain H37Rv. We found that neither the in vitro Mycobacterial Growth Inhibition Assay (MGIA) with splenocytes, nor the number of viable bacteria in the lung, indicated any ability of this vaccination protocol to reduce bacterial growth. We therefore conclude that these three specific PE/PPE proteins, while immunogenic in both humans and mice, are unable to drive protective immunity under these conditions.